East of Eden Television Production Still - Barney Rosenzweig Productions; Mace Neufeld Productions; Viacom Productions:::Creator::::::::::::; Hayman, Lee Richard (collector):::Contributor::::::::::::
The production crew campground during filming of water drilling scenes.Digital copy only. No hard copy.